2020
DOI: 10.1177/0269881120959614
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation in the rat prefrontal cortex and hippocampus after a single administration of psilocybin

Abstract: Background: Psilocybin is a serotonergic psychedelic found in “magic mushrooms” with a putative therapeutic potential for treatment-resistant depression, anxiety, obsessive-compulsive disorder, and addiction. In rodents, psilocybin acutely induces plasticity-related immediate early genes in cortical tissue; however, studies into the effects on subcortical regions, of different doses, and the subsequent translation of corresponding proteins are lacking. Methods: We examined the acute effects of a single adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 70 publications
3
61
1
1
Order By: Relevance
“…A recent study reported that psilocybin modulates neurotrophic-related gene expression in the PFC and hippocampus, with a preferential effect on the PFC, but inducing changes which are also appreciable in the hippocampus (Jefsen et al, 2020). More specifically, in the PFC psilocybin increased the expression of CEBPB, c-Fos, dual specificity protein phosphatase 1 (Dusp1), transcription factor jun-b, NF-kappa-b inhibitor-a (Ikba), nuclear receptor subfamily 4 group A member 1, while the serine/threonine-protein kinase 1 (Sgk1), protein fosB, protein S100-A10, and postsynaptic density protein 95 were increased only response to some doses of psilocybin.…”
Section: Psilocybinmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study reported that psilocybin modulates neurotrophic-related gene expression in the PFC and hippocampus, with a preferential effect on the PFC, but inducing changes which are also appreciable in the hippocampus (Jefsen et al, 2020). More specifically, in the PFC psilocybin increased the expression of CEBPB, c-Fos, dual specificity protein phosphatase 1 (Dusp1), transcription factor jun-b, NF-kappa-b inhibitor-a (Ikba), nuclear receptor subfamily 4 group A member 1, while the serine/threonine-protein kinase 1 (Sgk1), protein fosB, protein S100-A10, and postsynaptic density protein 95 were increased only response to some doses of psilocybin.…”
Section: Psilocybinmentioning
confidence: 99%
“…More specifically, in the PFC psilocybin increased the expression of CEBPB, c-Fos, dual specificity protein phosphatase 1 (Dusp1), transcription factor jun-b, NF-kappa-b inhibitor-a (Ikba), nuclear receptor subfamily 4 group A member 1, while the serine/threonine-protein kinase 1 (Sgk1), protein fosB, protein S100-A10, and postsynaptic density protein 95 were increased only response to some doses of psilocybin. Dual specificity protein kinase (CLK1) was dose dependently decreased in response to psilocybin (Jefsen et al, 2020). In the hippocampus, Dusp1, Ikba, and Sgk1 transcripts were similarly increased by acute psilocybin and Clk1 expression was strongly decreased (Jefsen et al, 2020).…”
Section: Psilocybinmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, molecular mechanisms underlying acute changes in brain activity and lasting psychological effects have been less investigated. Neuroplasticityrelated genes and immediate early genes have been reported to be over-expressed upon psychedelics' administration in rodent models, especially in areas with dense 5-HT2A receptor expression like the prefrontal cortex (Benekareddy et al, 2013;González-Maeso et al, 2003, 2007Jefsen et al, 2020;C. D. Nichols et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies, DMT suppressed 8–12 Hz (alpha) oscillations, whilst changes in the gamma range of oscillations correlated with some features of the reported ‘mystical’ experience. Further downstream, Jefsen et al (2021) investigate the acute effects of psilocybin on the expression of 46 neuroplasticity related genes in the prefrontal cortex and hippocampi of rats, showing rapid expression in plasticity promoting genes, more so in the prefrontal cortex (where 5-HT2A is densely expressed). Yet, 5-HT2A is but one modulator, and Inserra et al (2021) show that LSD modulates neuronal activity in both the reticular and mediodorsal thalamus in part due to its action as a type 2 dopamine receptor agonist.…”
mentioning
confidence: 99%